Comprehensive Assessment of the Global Burden and Risk Determinants of Otitis Media - Zubair, Sadia; Kausar, Tasleem; Aslam, Taskeen; Javed, Eman; Maryam, Musfira; Ahsan, Maryam; Naz, Amina; Ijaz, Uzma (BioScientific Review, 2026)
Otitis media (OM), a common inflammatory disease of the middle ear mostly affecting kids, is a serious global public health problem. Epidemiological studies indicate that early childhood sees at least one attack in up to 80% of children; the majority of incidents take place between the ages of six months to five years. One of the acute and chronic forms of the disease is Chronic Suppurative Otitis Media (CSOM), which strikes 3.8% of the world population, mostly in low- and middle-income countries. Major risk factors that provoke OM include smoking, weight, breastfeeding, socioeconomic status, genetic factors, and air pollution. Modifiable risk conditions of OM include adenoids, allergies, and craniofacial deformities. Though incidence is geographic, the burden of disease remains highest among underprivileged groups, where overcrowding, unhygienic conditions, and limited access to healthcare drive continuous infection and sequelae